(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the issues of implementing the methodology for developing conceptual thinking among students in the higher education process. Conceptual thinking is one of the essential skills that meets modern educational requirements. It enables students to deeply understand theoretical knowledge, identify logical connections between concepts, and systematize new information. The paper highlights pedagogical technologies, methodological approaches, and mechanisms for applying them in practice to foster conceptual thinking. The findings contribute to strengthening students’ creative and critical thinking abilities as well as preparing them for independent learning within the higher education system.